IGF2 and IGF1R identified as novel tip cell genes in primary microvascular endothelial cell monolayers - Dallinga, Marchien G. (Angiogenesis, 2018)
Tip cells, the leading cells of angiogenic sprouts, were identified in cultures of human umbilical vein endothelial cells (HUVECs) by using CD34 as a marker. Here, we show that tip cells are also present in primary human microvascular endothelial cells (hMVECs), a more relevant endothelial cell type for angiogenesis. By means of flow cytometry, immunocytochemistry, and qPCR, it is shown that endothelial cell cultures contain a dynamic population of CD34(+) cells with many hallmarks of tip cells, including filopodia-like extensions, elevated mRNA levels of known tip cell genes, and responsiveness to stimulation with VEGF and inhibition by DLL4. Furthermore, we demonstrate that our in vitro tip cell model can be exploited to investigate cellular and molecular mechanisms in tip cells and to discover novel targets for anti-angiogenesis therapy in patients. Small interfering RNA (siRNA) was used to knockdown gene expression of the known tip cell genes angiopoietin 2 (ANGPT2) and tyrosine kinase with immunoglobulin-like and EGF-like domains 1 (TIE1), which resulted in similar effects on tip cells and sprouting as compared to inhibition of tip cells in vivo. Finally, we identified two novel tip cell-specific genes in CD34(+) tip cells in vitro: insulin-like growth factor 2 (IGF2) and IGF-1-receptor (IGF1R). Knockdown of these genes resulted in a significant decrease in the fraction of tip cells and in the extent of sprouting in vitro and in vivo. In conclusion, this study shows that by using our in vitro tip cell model, two novel essential tip cells genes are identified. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10456-018-9627-4) contains supplementary material, which is available to authorized users.